How do people perceive organ donation?: using Q-methodology and post-Q survey to examine views on deceased organ donation in the UK - Muaid, Reem (2022)
There is a significant and chronically unmet need for donated organs from deceased donors. Despite generally positive views in the UK, donation rate remains low. It is imperative to understand what the public think about this issue if organ donation campaigns are to be effective and successful in addressing a particular group. This research investigates the public’s views through a subjective perception of a network of barriers and motivators. This research investigates the views on organ donation in the UK. This research is a mixed method research which consists of two studies: study one and two. Study one’s objective is to identify distinctive views on organ donation in the UK using Q-methodology and interviews. Q-methodology uses qualitative and quantitative methods to explore the subjective perceptions of people in relation to a particular subject. Forty participants sorted 47 statements on organ donation on a Q grid. Factor analysis was then conducted using Centroid method and Varimax rotation. Six views were found but only four views were interpreted: The Realist, the Optimist Hesitant, the Convinced Pessimist and the Empathetic. Salient barriers to organ donation presented in each view suggest that perceived lack of knowledge, death anxiety, mistrust in the healthcare system and lack of cue to action are the main barriers to organ donation. Consensus statements suggest that religion and family agreement are inconsequential if attitude to organ donation is well formed. Study two used post-Q survey method to identify the prevalence of each view in the UK. Self-categorisation to abbreviated factor descriptions (vignettes) method was used to transform Q-methodology views to four vignettes with 100-140 words each. A total of 385 participants were asked to rate and then rank four vignettes based on how much they reflect their view on organ donation. Results showed that the Empathetic view is the most common view in the UK, followed by the Realist, the Optimist Hesitant, and the Convinced Pessimist successively. Results suggest no relationship between views and other demographic, social and organ donation attitude criteria. This research demonstrated the importance of subjective perception in forming an attitude to organ donation. It suggests that ‘one size does not fit all’ when it comes to designing behavioural interventions, and subjective perception is an important variable in addressing low organ donation rate in the UK.